Physical Environmental Factors and Maternal Behavioral Characteristics in Toddlers ARI - Malik saepudin; Gebytri Nuraudia; Moh. Adib; Marvita; Windarti (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
ISPA frequently occurs in toddlers, particularly in the North Putussibau area, which reports the highest cases. This research studies the association between physical environmental factors and behaviors with ISPA incidence among toddlers at the North Putussibau Community Health Center. Using a case control design, 64 participants were equally separated into patient and comparison categories. Data were examined applying the χ2 analysis, with significance assessed correlations were among ISPA incidence and dampness (p = 0.023), lighting (p = 0.024), floor type (p = 0.000), residential density (p = 0.048), use of mosquito repellent (p = 0.003), exposure to smoke (p = 0.023), mothers not covering their mouths when coughing (p = 0.007), delayed toddler care (p = 0.003), and mothers not wearing masks when ill (p = 0.024). No significant links were observed with ventilation, wall or roof type, open windows, mothers not washing hands after coughing, or burning trash near the house. These results suggest that both the home environment and maternal behaviors influence the occurrence of sudden breathing illnesses in the young.